Improving VAT Compliance in Romania by Implementing a New Tool – Tax Lottery Receipts - Ungureanu, Dragos; Dascalu, Doina (Journal of Economic Development, Environment and People, 2015)
This paper aims to present and explain the newly implemented measure of organizing a Tax Lottery Receipts in Romania, in orderto combat tax evasion by raising awareness among consumers and make them responsible when purchasing any goods.The lottery proposes an approach to strengthen the fiscal voluntary conformation by stimulating financially those who promote respecting the law – asking for the fiscal receipt, and helpthe fiscal authorities this way in the fight against tax evasion, contrasting at the same time with punishing those who do not respect it – not issuing fiscal receipts.